2016
DOI: 10.18632/oncotarget.11714
|View full text |Cite
|
Sign up to set email alerts
|

An oncogenic role for sphingosine kinase 2

Abstract: While both human sphingosine kinases (SK1 and SK2) catalyze the generation of the pleiotropic signaling lipid sphingosine 1-phosphate, these enzymes appear to be functionally distinct. SK1 has well described roles in promoting cell survival, proliferation and neoplastic transformation. The roles of SK2, and its contribution to cancer, however, are much less clear. Some studies have suggested an anti-proliferative/pro-apoptotic function for SK2, while others indicate it has a pro-survival role and its inhibitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
76
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(83 citation statements)
references
References 49 publications
6
76
0
1
Order By: Relevance
“…In this situation there are less Type 2 raft domains (Cer enriched) and less apoptosis. Sphingosine kinases regulate a number of process which aid tumor progression such as survival, proliferation and transformation which therefore provide possible targets for therapy [72]. …”
Section: Lipid Alterations In Cancermentioning
confidence: 99%
“…In this situation there are less Type 2 raft domains (Cer enriched) and less apoptosis. Sphingosine kinases regulate a number of process which aid tumor progression such as survival, proliferation and transformation which therefore provide possible targets for therapy [72]. …”
Section: Lipid Alterations In Cancermentioning
confidence: 99%
“…Of the many enzymes responsible for the biosynthesis and metabolism of sphingolipids, the sphingosine kinases (SKs) are of particular interest to study as they catalyze the formation of sphingosine 1-phosphate (S1P), and in doing so can promote cell survival, proliferation, migration and angiogenesis 2 . Both sphingosine kinases, SK1 and SK2, have been shown to be upregulated in various human cancers and both have documented roles in mediating oncogenesis 3, 4 . However, where SK1 and its roles in cancer development are relatively well characterized, SK2 remains somewhat enigmatic as, in addition to the pro-cancer functions it shares with SK1, SK2 can also facilitate cell cycle arrest and cell death 5, 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, high-SK-2 cells express the enzyme mainly in the nucleus whereas low-SK-2 cells express the enzyme mainly in the cytosol and at the plasma membrane. The authors also showed that a modest (2.5-fold) upregulation of SK-2 occurs in a broad range of cancers which led them to suggest that indeed, inhibition of SK-2 may have an anti-cancer potential [35].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…In an attempt to explain the controversial results of SK-2 on proliferation and apoptosis of cancer cells, Neubauer et al proposed that the amount of SK-2 expression determines the cellular outcome [35]. This was based on studies performed in an inducible overexpression system where high-level overexpression of SK-2 in HEK293 cells (> 200-fold) reduced cell proliferation and survival, whereas low-level overexpression of SK-2 (in the range of 2-8-fold) promoted cell survival and proliferation [35].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
See 1 more Smart Citation